Reference study of IFC software support: The GeoBIM benchmark 2019—Part I. Issue 2 (2nd January 2021) - Noardo, Francesca; Krijnen, Thomas; Arroyo Ohori, Ken; Biljecki, Filip; Ellul, Claire; Harrie, Lars; Eriksson, Helen; Polia, Lorenzo; Salheb, Nebras; Tauscher, Helga; van Liempt, Jordi; Goerne, Hendrik; et al.
Abstract: Industry Foundation Classes (IFC), the buildingSMART open standard for BIM, is underused with respect to its promising potential, since, according to the experience of practitioners and researchers working with BIM, issues in the standard's implementation and use prevent its effective use. Nevertheless, a systematic investigation of these issues has never been carried out, and there is thus insufficient evidence for tackling the problems. The GeoBIM benchmark project is aimed at finding such evidence by involving external volunteers, reporting on various aspects of the behavior of tools (geometry, semantics, georeferencing, functionalities), analyzed and described in this article. Interestingly, different IFC software programs with the same standardized data sets yield inconsistent results, with few detectable common patterns, and significant issues are found in their support of the standard, probably due to the very high complexity of the standard data model. A companion article (Part II) describes the results of the benchmark related to CityGML, the counterpart of IFC within geoinformation.